Features of peripheral CD8+CD57+ lymphocytes in patients with autoimmune hemolytic anemia. (19th May 2018) - Fatone, Maria Celeste; Pavone, Fabio; Lauletta, Gianfranco; Russi, Sabino
Abstract: Autoimmune hemolytic anemia (AIHA) is an acquired condition characterized by the presence of autoantibodies recognizing erythrocyte-related antigens. Several components of the immune system are involved in disease pathogenesis. Among them, as for other autoimmune disorders, a role for specific CD8 + CD57 + regulatory cells subset could be hypothesized. We evaluated this lymphocyte subset by flow cytometry in 18 AIHA patients randomly selected in a retrospective population of 29 cases. Secondary forms were observed in 65.5% of cases, whereas frequencies of warm, cold, mixed, and atypical forms were similar. Cold agglutinins and cryoglobulins tested positive in 44.8% and 10.3% of cases, respectively. These patients exhibited a higher frequency of peripheral vascular symptoms (odds ratio = 8.2, p = .04) and complement consumption (odds ratio = 7.2, p = .02). Frequency of CD8 + CD57 + cells resulted significantly higher in AIHA patients than in control group (17.0 ± 15.8% vs 8.2 ± 5.0%, p = .04). Regardless of therapeutic schedule, patients with partial or no response to therapy (8/18) showed higher frequencies of CD8 + CD57 + cells as compared with controls (23.6 ± 21.3% vs 8.9 ± 4.9%, p = .01), whereas 10/18 complete responders (CR) showed lower levels of CD8 + CD57 + cells (11.7 ± 6.9%, p = .11). CR and controls showed similar values ( p = .24). This study suggests that monitoring this lymphocyte subset before and after treatment administration might have a prognostic value. Moreover, CD8 + CD57 + cells may represent a possible therapeutic target to restore the normal balance between lymphocyte populations.